Detecting lateral composition modulation in dilute Ga(As, Bi) epilayers. (30th September 2015) - Wu, Mingjian; Hanke, Michael; Luna, Esperanza; Puustinen, Janne; Guina, Mircea; Trampert, Achim
Abstract: The ability to characterize a structure into the finest details in a quantitative manner is a key issue to understanding and controlling nanoscale phase separation in novel nanomaterials. In this work, we consider the detectability of lateral composition modulation (LCM), a type of nanoscale phase separation in GaAs1− x Bi x epilayers, by x-ray diffraction (XRD). We show that the satellite peaks due to LCM are hardly detectable in reasonable time with a lab x-ray diffractometer for GaAs1− x Bi x samples with an average x up to 25% and relative modulation up to 50%. This is in contrast to LCM reported in other III-V combinations, where the intensity of the satellite peak is relatively high and can be easily detected. Our theoretical considerations are complemented experimentally using highly brilliant synchrotron radiation. The results are in good agreement with the predictions. This work provides a guideline for the systematic characterization of LCM in zincblende III-V semiconductor epilayers and points to the critical role of quantitative characterization of nanoscale phase separation.